'COVID containers' in pandemic mediascapes: discursive economies of health, bodies, and race in North America. Issue 3 (3rd July 2022) - (Cal) Biruk, Crystal
Abstract: Bringing an ethnographic sensibility to pandemic mediascapes, this article critically examines three media artifacts that assembled around COVID-19 – as an entity that is viral, social, and political – in the early months of the pandemic in North America. Focusing on the household, the cruise ship, and the body-with-underlying-conditions as 'COVID containers', the author argues that material and discursive responses to the pandemic, articulated through imaginaries of containers and containment, uphold notions of risk, order, and health that garner meaning through implied racial intertexts. The article analyzes COVID-19-related data, graphics, talk, and news stories to show how logics of inside/outside, safety/risk, and comfort/fear that animate efforts to contain a viral threat intensify the pathologization, harm, surveillance, and risk of groups long imagined as 'threats' to social order. Throughout, The author demonstrates how idioms of containers and containment make 'the body' a key locus of health, diverting attention from systems and histories complicit in producing ill-health. A coda reflects on Scheper-Hughes and Lock's influential essay ' The mindful body', re-reading their articulation of the 'Western body' through lenses drawn from scholarship in Black studies, queer studies, and disability studies that are central to understanding COVID-19 as relation(s) – borne from racial capitalism – that differentially distribute risk, health, and care.